Case report: A rare EBV-associated T/NK cell monomorphic posttransplant lymphoproliferative disorder - Jiang, Xin; Zhang, Yao-Yu; Li, Xiao-Wei; Li, Xiao-Dong; Li, Zhan-Yuan; Meng, Wen-Jun; Li, Sha-Dan (Frontiers in Immunology, 2024)
Background: Kidney transplantation (KT) is the best treatment for patients with end-stage renal disease. However, postoperative complications remain the main issues faced during KT recovery period. Posttransplant lymphoproliferative disorders (PTLD) are one of the severe and life-threatening complications that occur after KT while the recipient is undergoing immunosuppressive therapy. PTLD risk factors include Epstein-Barr virus (EBV) infection, the cumulative degree of immunosuppression, as well as genetic aspects. PTLD is more common in the transplanted organ itself and its surroundings, and the central nervous system, while PTLD involving the pharyngeal soft tissue is relatively rare, with only a few reported case reports. Therefore, systematic experience is scarce regarding whether the treatment or the care.Case presentation: Herein, we report a 41-year-old male, underwent a reproductive KT due to chronic renal insufficiency. Recurrent fever, pharyngeal pain, and bilateral cervical lymph node enlargement were recurred during five years' follow-up after KT surgery. In this inpatient experience, the patient vomited a large amount of blood from the oropharynx, then the tonsil artery was ligated by emergency operation. EBV-associated T/NK cell monomorphic PTLD was eventually diagnosed by blood EBV DNA test, pharyngeal biopsy, and corresponding pathological examination. After six cycles of R-CHOP chemotherapy, the clinical symptoms and laboratory tests changed into normal. Subsequent three years' follow-up shows no tumor recurrence and good transplant kidney function.This rare case report describes a manifestation of PTLD with pharyngeal involvement. Early diagnosis using histopathological examination is crucial to prevent damage to the throat and airway, and even life-threatening conditions. Discontinuing immunosuppression and starting systemic treatment can help in disease regression. Since the low incidence of this disease, limited clinical experience, and limited data, our experience with a smooth recovery through efficacy treatment and nursing can provide a reference for the development of new clinical drugs and diagnostic and treatment plans of patients with PTLD in the future.